Digital Museology Under Test: Challenges and Opportunities for Russian Museums - Guboglo, Anna (Museum and Society, 2020)
The short article explores new aspects of digital museology that become apparent during the global COVID-19 crisis, drawing on the experience of Russian museum activity. Under the circumstances of complete digitization, the digital sphere becomes the sole possibility for the economic survival of a whole group of cultural organizations, but also provides an opportunity for the establishment of new roles of the museum in society.